2016
DOI: 10.3390/ijerph13020231
|View full text |Cite
|
Sign up to set email alerts
|

Sunbed Use Prevalence and Associated Skin Health Habits: Results of a Representative, Population-Based Survey among Austrian Residents

Abstract: Abstract:Recreational sunbed use accounts for the main non-solar source of exposure to ultraviolet radiation in fair-skinned Western populations. Indoor tanning is associated with increased risks for acute and chronic dermatological diseases. The current community-based study assessed the one-year prevalence of sunbed use and associated skin health habits among a representative, gender-balanced sample of 1500 Austrian citizens. Overall one-year prevalence of sunbed use was 8.9% (95% confidence interval (CI) 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
23
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 56 publications
12
23
1
2
Order By: Relevance
“…The reasons for this, especially the desire for a tan and a specific body image by young women, have been found in studies from Northern Europe and Australia, too . The current numbers from this study's initial observation phase correspond to an Austrian study on the use of sunbeds in which the 1‐year prevalence was 8.9%, and sunbed use was slightly higher in women than in men . Moreover, extrinsic ageing and skin type were major predictors for sunbed use or abuse, which was corroborated in the current study.…”
Section: Discussionsupporting
confidence: 84%
“…The reasons for this, especially the desire for a tan and a specific body image by young women, have been found in studies from Northern Europe and Australia, too . The current numbers from this study's initial observation phase correspond to an Austrian study on the use of sunbeds in which the 1‐year prevalence was 8.9%, and sunbed use was slightly higher in women than in men . Moreover, extrinsic ageing and skin type were major predictors for sunbed use or abuse, which was corroborated in the current study.…”
Section: Discussionsupporting
confidence: 84%
“…Indoor tanning is more frequent in sporty than non‐sporty individuals, in smokers than in non‐smokers, and in current than former smokers. This has been shown in European studies investigating both adults and adolescents . A significant link between sunbed use and other unhealthy lifestyle factors (abuse of alcohol/drugs, unbalanced nutritional habits) had been reported by American studies, and recently was confirmed by a large Danish investigation on 64 000 students .…”
Section: Who Uses Sunbeds In Europementioning
confidence: 56%
“…Many European studies have clearly shown that the vast majority of indoor tanners are sun‐seekers. Sunbed users have reported more frequently than non‐users a number of sun‐seeking behaviours such as intentional sun exposure, especially at peak hours; sun protection habits, including sunscreen and sunglasses but not protective clothes; nudism; outdoor hobbies; intensive lifetime sun exposure; and multiple sunburns during life . These data suggest that sunbed users are likely to receive the highest possible cumulative dose of UV radiation during their lifetime.…”
Section: Who Uses Sunbeds In Europementioning
confidence: 96%
See 1 more Smart Citation
“…However, it is our strong conviction that statements would improve when they are based on unambiguous exposure data. The large amount of uncertainty among the general public regarding UV exposure [78,79] underlines this need very strongly.…”
Section: Discussionmentioning
confidence: 99%